LONG-TERM field study of a Waterborne paint with a nano-additive for biodeterioration control - Gámez Espinosa, Erasmo Junior (2022)
Biodeterioration in building façades represents an important economic loss related to maintaining a functional protective coating system. Research papers with long-time studies on paint performance exposed to field conditions are scarce. Fungi, cyanobacteria, and algae are frequently present in biofilms formed in outdoor locations. Among these, defacement caused by fungi is known for the broad damage spectrum produced. Therefore, it is important to extend the service life of the protective coatings systems. To reach this goal, studies that consider the action of both biotic and abiotic factors acting simultaneously for prolonged periods are necessary. The present research work presents the assessment carried out on acrylic outdoor paint with a nano-additive exposed to long-term field conditions. Paint with 1% by weight of ZnO particles with nano-sized crystallites (nano-additive) was exposed to natural weathering. Samples with north and south orientation were evaluated by long-term field studies during a period of four years. The incorporation of the nano-additive proved to extend service life. In the paints facing north, the ZnO particles were more efficient for the biodeterioration control.